Method for preparing high-capacity fast-charging graphite by integrating liquid-phase fusion and gas-phase coating
Patent Information
- Application Number
- CN202611508252.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-28
- Publication Date
- 2026-10-30
AI Technical Summary
但该工艺仅能实现表面改性,无法优化石墨内部晶粒结构与孔隙结构,石墨内部储锂位点不足、离子传输通道单一,难以大幅提升材料比容量,容量上限受限,无法兼顾高容量与快充双重需求
[0020]1、本发明通过液相渗透融合改性和一体化原位气相包覆,摒弃传统分步制备模式,首先采用液相改性体系对石墨基体进行浸润、掺杂、低温融合预处理,实现改性组分均匀渗透至石墨晶粒间隙与内部孔隙,重构石墨内部微观结构,构建丰富的储锂位点与连续的离子传输通道,提升材料储锂容量;随后无需出料冷却,直接在同一反应设备内升温切换气相沉积氛围,在液相融合改性后的石墨基体表面原位生长均匀、致密、结合力强的碳包覆层,修复表面缺陷、降低界面阻抗、抑制电解液副反应,大幅提升材料快充能力与循环稳定性;两步工艺无缝衔接、一体化完成,无中间转运、二次加工环节,兼顾结构改性效果与量产优势。
Smart Images

Figure CN123017952A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of graphite anode material technology, specifically a method for preparing high-capacity fast-charging graphite by integrating liquid-phase fusion and gas-phase coating. Background Technology
[0002] Graphite anode materials have long been the mainstream choice for lithium-ion battery anode materials due to their advantages such as good conductivity, low lithium intercalation potential, and excellent cycle stability. However, with the rapid development of new energy vehicles and energy storage systems, the market is placing increasingly higher demands on the energy density and fast-charging performance of lithium-ion batteries, posing a severe challenge to the lithium storage capacity and rate performance of graphite anode materials.
[0003] To improve the electrochemical performance of graphite anode materials, the industry currently mainly adopts two technical routes: liquid-phase modification and gas-phase coating.
[0004] Single-phase liquid-phase doping fusion is a common modification method, which mainly uses liquid-phase solvent mixing and high-temperature sintering to modify graphite. It can improve the compaction density and lithium storage capacity of graphite by doping with active materials. However, after modification, the graphite surface has many defects, uneven pore distribution, poor interface stability, and the electrolyte is easily decomposed and consumed. This leads to severe polarization and poor rate performance during fast charging, and rapid cycle decay under high current charge and discharge.
[0005] Single-phase carbon coating is another mainstream technology. It constructs a carbon coating layer on the graphite surface through vapor deposition, which can effectively repair graphite surface defects, optimize interface structure, and improve conductivity and fast charging capability. However, this process can only achieve surface modification and cannot optimize the internal grain structure and pore structure of graphite. The graphite has insufficient lithium storage sites and a single ion transport channel, making it difficult to significantly improve the specific capacity of the material. The capacity limit is limited, and it cannot meet the dual requirements of high capacity and fast charging.
[0006] In addition, there are a few technical solutions in the industry that adopt a step-by-step preparation method of "liquid phase modification + vapor phase coating". However, this type of solution requires multiple processes to be completed independently, such as liquid phase sintering, cooling and sieving, vapor phase deposition, and secondary heat treatment. It has problems such as complicated process flow, high production energy consumption, secondary material contamination, poor batch consistency, and weak bonding between coating layer and substrate. At the same time, step-by-step high-temperature treatment is prone to excessive sintering of graphite grains and structural collapse, which deteriorates fast charging performance and cycle life, resulting in high mass production cost and low yield.
[0007] In summary, existing graphite preparation technologies cannot simultaneously achieve internal structure optimization and capacity enhancement, as well as surface interface modification and fast charging. These technologies suffer from technical bottlenecks such as mutual constraints between capacity and fast charging performance, cumbersome processes, and poor mass production stability. There is an urgent need to develop an integrated, efficient, and mass-producible modification preparation technology to simultaneously improve the capacity, fast charging performance, and cycle stability of graphite anodes. Summary of the Invention
[0008] The purpose of this invention is to provide a method for preparing high-capacity fast-charging graphite by integrating liquid-phase fusion and gas-phase coating, so as to solve the problems mentioned in the background art.
[0009] To achieve the above objectives, the present invention provides the following technical solution: a method for preparing high-capacity fast-charging graphite by integrating liquid-phase fusion and gas-phase coating, comprising the following steps: S1. Pretreatment of graphite matrix: Place the graphite matrix in a vacuum drying oven and vacuum dry at 120-150℃ for 4-6 hours to obtain graphite powder. S2. Preparation of functional liquid phase modification system: Mix the modified carbon source, high capacity dopant and dispersing solvent evenly according to the mass ratio to prepare a uniform and stable liquid phase modification system. S3. Liquid-phase infiltration and fusion modification: Pretreated graphite powder is added to a liquid-phase modification system and stirred at 1200-2000 rpm for 30-60 minutes at room temperature to ensure the liquid-phase modification system fully wets the graphite powder and penetrates into the internal pores and intergranular spaces of the graphite. Subsequently, in a closed high-temperature and high-pressure reactor, the pressure is increased to 1.5-4.0 MPa by inert gas, the temperature is raised to 180-250℃, and held at a constant temperature for 2-4 hours to complete the low-temperature fusion reaction of the liquid phase. This allows the liquid-phase modification system to tightly bond with the internal granular spaces of the graphite powder, reconstructing the internal porous transport structure, increasing lithium storage active sites, and obtaining a liquid-phase fusion modified graphite intermediate. S4. Integrated in-situ gas phase coating: After the liquid phase fusion reaction is completed, the pressure is released in the same reaction equipment and switched to an inert atmosphere and heated. A mixture of gas phase carbon source and inert carrier gas is introduced for gas phase deposition coating. A uniform and dense carbon coating layer is grown in-situ on the surface of the liquid phase fusion modified graphite intermediate. After the reaction is completed, it is naturally cooled to room temperature in an inert atmosphere. S5. Post-processing and molding: After natural cooling to room temperature, the material is sequentially screened, iron removed, and purified to obtain a high-capacity fast-charging graphite anode material.
[0010] In step S1, the graphite matrix is one of natural graphite micro powder and artificial graphite powder.
[0011] In step S1, the particle size D50 of the graphite matrix powder is 8-15 μm.
[0012] In step S2, the mass ratio of each component in the liquid-phase modification system is as follows: 5%-12% modified carbon source, 2%-5% high-capacity doping agent, and the remainder is dispersion solvent.
[0013] In step S2, the modified carbon source is selected from one or more of sucrose, glucose, phenolic resin liquid and asphalt solution.
[0014] In step S2, the high-capacity doping agent is selected from one or more of nano-silicon oxide, lithium titanate, and porous carbon micropowder.
[0015] In step S2, the dispersing solvent is a mixture of anhydrous ethanol and deionized water, wherein the volume ratio of anhydrous ethanol to deionized water is 1:1.
[0016] In step S3, the solid-liquid mass ratio of the graphite powder to the liquid-phase modification system is 1:3-5.
[0017] In step S4, the inert atmosphere is either nitrogen or argon. The heating rate is 5-10℃ / min, and the temperature is increased to 800-950℃; The gaseous carbon source is selected from one or more of propylene, acetylene, and methane; The gaseous carbon source accounts for 10%-20% of the volume in the mixed gas. The vapor deposition coating time is 1.5-3 hours.
[0018] In step S4, the thickness of the carbon coating layer is 20-50 nm.
[0019] Compared with the prior art, the beneficial effects of the present invention are:
[0020] 1. This invention abandons the traditional step-by-step preparation mode by using liquid-phase infiltration fusion modification and integrated in-situ vapor phase coating. First, a liquid-phase modification system is used to wet, dope, and perform low-temperature fusion pretreatment on the graphite matrix, so that the modified components can be uniformly penetrated into the intergranular spaces and internal pores of the graphite, reconstructing the internal microstructure of the graphite, building abundant lithium storage sites and continuous ion transport channels, and improving the lithium storage capacity of the material. Then, without the need for material discharge and cooling, the temperature is directly increased and the vapor phase deposition atmosphere is switched in the same reaction equipment to grow a uniform, dense, and strongly bonded carbon coating layer in situ on the surface of the liquid-phase fusion modified graphite matrix, repairing surface defects, reducing interfacial impedance, and suppressing electrolyte side reactions, which greatly improves the material's fast charging capability and cycle stability. The two-step process is seamlessly connected and completed in one step, without intermediate transfer or secondary processing links, taking into account both the structural modification effect and the advantages of mass production.
[0021] 2. This invention achieves synergistic modification of graphite inside and out. The internal structure is constructed by liquid phase doping and fusion to build a porous high lithium storage structure, thereby improving the specific capacity of the material. The surface is constructed by in-situ gas phase coating to build a low impedance stable interface, thereby improving fast charging performance and cycle stability, and completely solving the pain point of mutual restriction between capacity and fast charging performance of traditional graphite. Attached Figure Description
[0022] Figure 1 This is a SEM image of the cross-section of graphite particles before liquid-phase infiltration and fusion modification in Example 1 of the present invention;
[0023] Figure 2 This is a SEM image of the cross-section of graphite particles after liquid-phase infiltration and fusion modification in Example 1 of the present invention;
[0024] Figure 3 This is a TEM image of the cross-section of the surface coating layer after vapor phase coating in Embodiment 1 of the present invention;
[0025] Figure 4 The graphite XRD pattern before liquid-phase infiltration and fusion modification in Example 1 of this invention;
[0026] Figure 5 The image shows the XRD pattern of graphite after liquid-phase infiltration and fusion modification in Example 1 of this invention.
[0027] Figure 6 This is a comparison graph of the charge / discharge voltage-capacity of the test batteries in the embodiments of the present invention and the comparative test batteries;
[0028] Figure 7 This is a graph showing the negative electrode potential-SOC relationship between the test cells in the embodiments and comparative examples of the present invention.
[0029] Figure 8 This is a graph showing the cycle capacity retention rate of the batteries used in the embodiments and comparative tests of this invention.
[0030] Figure 9 This is a graph showing the cycle capacity decay rate of the batteries used in the embodiments and comparative tests of this invention. Detailed Implementation
[0031] The technical solutions in the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments.
[0032] In this invention, the same reaction equipment used in steps S3 and S4 is a high-temperature and high-pressure reactor, which can achieve stirring under high temperature and high pressure, and seamlessly connect liquid-phase fusion and gas-phase coating within the same equipment. Specifically, the high-temperature and high-pressure reactor includes a vessel body, an electric heating wire, a stirrer, an air inlet system, an exhaust system, a pressure detection and control unit, a temperature detection and control unit, a condensation recovery unit, and a safety pressure relief unit; the maximum heating temperature of the electric heating wire is not lower than 1000℃; the stirrer is a magnetically coupled stirrer, with a stirring rate of 1200-2000 rpm during the liquid-phase penetration and fusion modification stage, and a stirring rate of 0-50 rpm or stopped during the gas-phase coating stage; the air inlet system is connected to an inert gas source and a gaseous carbon source respectively, and through a cutting... The valve is changed to achieve inert pressurization in the liquid-phase permeation fusion modification stage and mixed intake of carbon source / carrier gas in the gas phase coating stage; the exhaust system is connected to the condenser and tail gas treatment device; in the liquid-phase permeation fusion modification stage, after the reactor is sealed, it is pressurized to 1.5-4.0MPa with inert gas to keep the anhydrous ethanol-deionized water mixed solvent in a liquid phase or subcritical state at 180-250℃, avoiding premature vaporization and escape of the solvent; after the liquid-phase fusion reaction is completed, the reactor is depressurized to 0-0.2MPa, switched to an inert atmosphere, and heated to 800-950℃ at 5-10℃ / min, and a mixed gas of gas phase carbon source and inert carrier gas is introduced for chemical vapor deposition coating, realizing seamless connection between liquid-phase fusion and gas phase coating in the same equipment.
[0033] Example 1
[0034] A method for preparing high-capacity fast-charging graphite by integrating liquid-phase fusion and gas-phase coating includes the following steps: S1. Pretreatment of graphite matrix: Natural graphite powder with D50=10μm was selected as the graphite matrix. The graphite matrix was placed in a vacuum drying oven and vacuum dried at 130℃ for 5h to remove moisture and impurities, and graphite powder was obtained. S2. Preparation of functional liquid phase modification system: Mix 8% phenolic resin liquid, 3% nano silica additive, and 89% dispersion solvent (anhydrous ethanol and deionized water mixed in a volume ratio of 1:1) evenly to prepare a uniform and stable liquid phase modification system. S3. Liquid-phase infiltration and fusion modification: Pretreated graphite powder is added to a liquid-phase modification system with a solid-liquid mass ratio of 1:4. At room temperature, the mixture is stirred and dispersed at 1500 rpm for 40 minutes to ensure that the liquid-phase modification system fully wets the graphite powder and penetrates into the internal pores and intergranular spaces of the graphite. Subsequently, the mixture is transferred to a high-temperature and high-pressure reactor, sealed, and pressurized to 2.5 MPa by argon gas. The temperature is then raised to 200°C and held at this temperature for 3 hours to complete the low-temperature fusion reaction of the liquid phase. This process tightly binds the liquid-phase modification system with the internal granular spaces of the graphite powder, reconstructs the internal porous transport structure, increases lithium storage active sites, and yields a liquid-phase fusion modified graphite intermediate. S4. Integrated in-situ vapor phase coating: After the liquid phase fusion reaction is completed, the pressure is released to 0-0.2MPa in the same reaction equipment, the atmosphere is switched to argon, and the temperature is raised to 880℃ at a heating rate of 8℃ / min. Then, a mixture of argon and propylene gas (propylene volume ratio of 15%) is introduced for vapor phase deposition coating for 2 hours. A uniform and dense carbon coating layer is grown in situ on the surface of the liquid phase fusion modified graphite intermediate. After the reaction is completed, it is naturally cooled to room temperature in an inert atmosphere. S5. Post-processing and molding: After natural cooling to room temperature, the material is sequentially screened, iron removed, and purified to obtain a high-capacity fast-charging graphite anode material.
[0035] Example 2
[0036] A method for preparing high-capacity fast-charging graphite by integrating liquid-phase fusion and gas-phase coating includes the following steps: S1. Pretreatment of graphite matrix: Natural graphite powder with D50=12μm was selected as the graphite matrix. The graphite matrix was placed in a vacuum drying oven and vacuum dried at 140℃ for 4h to remove moisture and impurities, and graphite powder was obtained. S2. Preparation of functional liquid phase modification system: Mix 10% asphalt solution, 4% lithium titanate additive, and 86% dispersion solvent (anhydrous ethanol and deionized water mixed in a volume ratio of 1:1) evenly to prepare a uniform and stable liquid phase modification system. S3. Liquid-phase infiltration and fusion modification: Pretreated graphite powder is added to a liquid-phase modification system with a solid-liquid mass ratio of 1:3.5. The mixture is stirred and dispersed at 1800 rpm for 50 minutes at room temperature to ensure that the liquid-phase modification system fully wets the graphite powder and penetrates into the internal pores and intergranular spaces of the graphite. Subsequently, the mixture is transferred to a high-temperature and high-pressure reactor, sealed, and pressurized to 3.0 MPa with argon gas. The temperature is then raised to 200°C and held at this temperature for 3.5 hours to complete the low-temperature fusion reaction of the liquid phase. This process tightly binds the liquid-phase modification system with the internal granular spaces of the graphite powder, reconstructs the internal porous transport structure, increases lithium storage active sites, and yields a liquid-phase fusion modified graphite intermediate. S4. Integrated in-situ vapor phase coating: After the liquid phase fusion reaction is completed, the pressure is released to 0-0.2MPa in the same reaction equipment, the atmosphere is switched to argon, and the temperature is raised to 900℃ at a heating rate of 6℃ / min. Then, a mixture of argon and methane (methane volume percentage 12%) is introduced for vapor phase deposition coating for 2.5h. A uniform and dense carbon coating layer is grown in situ on the surface of the liquid phase fusion modified graphite intermediate. After the reaction is completed, it is naturally cooled to room temperature in an inert atmosphere. S5. Post-processing and molding: After natural cooling to room temperature, the material is sequentially screened, iron removed, and purified to obtain a high-capacity fast-charging graphite anode material.
[0037] Comparative Example 1
[0038] The method for fast-charging graphite includes the following steps: S1. Pretreatment of graphite matrix: Natural graphite powder with D50=10μm was selected as the graphite matrix. The graphite matrix was placed in a vacuum drying oven and vacuum dried at 130℃ for 5h to remove moisture and impurities, and graphite powder was obtained. S2. Preparation of functional liquid phase modification system: Mix 8% phenolic resin liquid, 3% nano silica additive, and 89% dispersion solvent (anhydrous ethanol and deionized water mixed in a volume ratio of 1:1) evenly to prepare a uniform and stable liquid phase modification system. S3. Liquid-phase infiltration and fusion modification: Pretreated graphite powder is added to a liquid-phase modification system with a solid-liquid mass ratio of 1:4. At room temperature, the mixture is stirred and dispersed at 1500 rpm for 40 minutes to ensure that the liquid-phase modification system fully wets the graphite powder and penetrates into the internal pores and intergranular spaces of the graphite. Subsequently, the mixture is transferred to a high-temperature and high-pressure reactor, sealed, and pressurized to 2.5 MPa by argon gas. The temperature is then raised to 200°C and held at this temperature for 3 hours to complete the low-temperature fusion reaction of the liquid phase. This process tightly binds the liquid-phase modification system with the internal granular spaces of the graphite powder, reconstructs the internal porous transport structure, increases lithium storage active sites, and yields a liquid-phase fusion modified graphite intermediate. S4. Post-processing and molding: The liquid-phase fusion modified graphite intermediate obtained above is screened, iron removed, and purified to obtain graphite anode material.
[0039] The difference between this comparative example and Example 1 is that the integrated in-situ vapor phase coating process is not performed, but the parameters of the remaining steps are the same, and a single liquid phase modified graphite material is prepared.
[0040] Comparative Example 2
[0041] The method for fast-charging graphite includes the following steps: S1. Pretreatment of graphite matrix: Natural graphite powder with D50=10μm was selected as the graphite matrix. The graphite matrix was placed in a vacuum drying oven and vacuum dried at 130℃ for 5h to remove moisture and impurities, and graphite powder was obtained. S2. Vapor phase coating: After the graphite matrix pretreatment is completed, it is transferred to a vapor phase deposition equipment. The vapor phase deposition equipment is switched to an argon atmosphere and heated to 880°C at a heating rate of 8°C / min. Then, a mixture of argon and propylene gas (propylene volume ratio of 15%) is introduced for vapor phase deposition coating for 2 hours. A uniform and dense carbon coating layer is grown in situ on the surface of the graphite powder. After the reaction is completed, it is naturally cooled to room temperature under an inert atmosphere. S3. Post-processing and molding: After natural cooling to room temperature, the material is sequentially sieved, iron removed, and purified to obtain graphite anode material.
[0042] The difference between this comparative example and Example 1 is that the liquid phase infiltration and fusion modification process is not performed, while the parameters of the remaining steps are the same, and a single gas phase coated graphite material is prepared.
[0043] Comparative Example 3
[0044] The preparation method of fast-charging graphite adopts a traditional step-by-step process, including the following steps: S1. Pretreatment of graphite matrix: Natural graphite powder with D50=10μm was selected as the graphite matrix. The graphite matrix was placed in a vacuum drying oven and vacuum dried at 130℃ for 5h to remove moisture and impurities, and graphite powder was obtained. S2. Preparation of functional liquid phase modification system: Mix 8% phenolic resin liquid, 3% nano silica additive, and 89% dispersion solvent (anhydrous ethanol and deionized water mixed in a volume ratio of 1:1) evenly to prepare a uniform and stable liquid phase modification system. S3. Liquid-phase infiltration and fusion modification: Pretreated graphite powder is added to a liquid-phase modification system with a solid-liquid mass ratio of 1:4. At room temperature, the mixture is stirred and dispersed at 1500 rpm for 40 minutes to ensure that the liquid-phase modification system fully wets the graphite powder and penetrates into the internal pores and intergranular spaces of the graphite. Subsequently, the mixture is transferred to a high-temperature and high-pressure reactor, sealed, and pressurized to 2.5 MPa by argon gas. The temperature is then raised to 200°C and held at this temperature for 3 hours to complete the low-temperature fusion reaction of the liquid phase. This process tightly binds the liquid-phase modification system with the internal granular spaces of the graphite powder, reconstructs the internal porous transport structure, increases lithium storage active sites, and yields a liquid-phase fusion modified graphite intermediate. S4. Discharge, cooling, and sieving: After cooling the above-mentioned liquid-phase fused modified graphite intermediate to room temperature, discharge it and perform sieving. S5. Vapor phase coating: The sieved graphite intermediate is transferred into a vapor phase deposition equipment. The vapor phase deposition equipment is switched to an argon atmosphere and heated to 880°C at a heating rate of 8°C / min. Then, a mixture of argon and propylene gas (propylene volume percentage 15%) is introduced for vapor phase deposition coating for 2 hours. After the reaction is completed, it is naturally cooled to room temperature under an inert atmosphere. S6. Post-processing and molding: After natural cooling to room temperature, the material is sequentially sieved, iron removed, and purified to obtain graphite anode material.
[0045] The difference between this comparative example and Example 1 is that the traditional stepwise process is used. First, the liquid phase penetration fusion modification process of Example 1 is completed. Then, after the material is discharged, cooled, and sieved, it is transferred to a vapor phase deposition device to complete the vapor phase coating. The remaining parameters are the same as those of Example 1, and the traditional stepwise modified graphite material is prepared.
[0046] Experimental Example
[0047] Electrochemical performance tests and physicochemical property characterizations were performed on the products of Examples 1-2 and Comparative Examples 1-3 above. The test system was a coin cell, and the specific test methods are as follows: The graphite anode materials obtained in each embodiment and comparative example were mixed with a conductive agent (Super P) and a binder (PVDF) at a mass ratio of 8:1:1. N-methylpyrrolidone (NMP) was added and stirred until homogeneous to form a slurry. This slurry was coated onto a copper foil current collector, dried, rolled, and cut to form the anode sheet. Using a lithium metal sheet as the counter electrode, Celgard 2400 as the separator, and 1 mol / L LiPF6 / EC+DEC (volume ratio 1:1) as the electrolyte, CR2032 coin cells were assembled in an argon glove box. Electrochemical performance was tested using a Blue Battery testing system, with a voltage range of 0.005-2.0V.
[0048] I. Microscopic morphology and structural characterization;
[0049] 1. Figure 1 and Figure 2 The images shown are cross-sectional SEM images of graphite particles before and after liquid-phase infiltration fusion modification in Example 1. Figure 1 As can be seen, the unmodified raw graphite particles exhibit numerous wide gaps, obvious cracks, and particle warping and separation; the particles are aggregated and stacked, with significant cracking at the particle interfaces, particle deformation and misalignment, uneven internal pore size, and numerous large-sized cracks. Figure 2It is evident that after liquid-phase infiltration and fusion modification, the graphite particles are tightly bonded together, with no obvious large cracks or large-area particle peeling and warping; only a small number of fine and uniform micropores exist. The nano-silica dopant is uniformly infiltrated into the gaps between graphite grains and the internal pores, indicating that the liquid-phase modification system has successfully achieved infiltration and fusion reconstruction inside the graphite, providing a structural basis for improving lithium storage capacity.
[0050] 2. Figure 3 The image shows a cross-sectional TEM image of the surface coating layer after vapor phase coating in Example 1. As can be seen from the image, a uniform carbon coating layer is formed on the surface of the graphite substrate. The coating layer is continuous, uniform, and dense, and is tightly bonded to the graphite substrate without cracks, indicating that the integrated vapor phase coating process of the present invention can effectively construct a high-quality surface coating layer.
[0051] 3. Figure 4 and Figure 5 The images show the XRD patterns of graphite before and after liquid-phase infiltration fusion modification in Example 1. Comparing the two images, it can be seen that the position and intensity of the (002) characteristic peak of the modified graphite have changed to some extent, and the interlayer spacing (d002) has increased. This is related to the entry of the dopant into the interlayer or grain gap of the graphite. At the same time, the degree of graphitization remains good, indicating that the liquid-phase fusion modification has achieved doping compatibilization without damaging the main lattice structure of the graphite.
[0052] 4. Raman spectroscopy tests were performed on the products of each embodiment and comparative example. The ID / IG ratio results are as follows: 0.28 for Example 1, 0.30 for Example 2, 0.45 for Comparative Example 1, 0.35 for Comparative Example 2, and 0.38 for Comparative Example 3. The results show that the ID / IG ratio of the product of the embodiment of the present invention is significantly lower than that of the comparative examples, indicating that the vapor-phase coating layer effectively repairs the defects on the graphite surface and reduces the surface disorder.
[0053] II. Electrochemical performance testing;
[0054] 1. Battery charge / discharge voltage-capacity curve performance (see...) Figure 6 ): As can be seen from the graph, the curve is divided into two main segments: the charging segment (the voltage rises from 0Ah to 2.5Ah) and the discharging segment (the voltage drops back from high capacity to 0Ah). The charging process (upper part of the figure, voltage range of 3.4V-3.7V): Starting from 0Ah, the voltage rises rapidly, then enters a gradual charging plateau. Example 1 shows the highest overall charging plateau voltage; Example 2 is next; the three comparative examples show lower plateau voltages. A higher charging plateau indicates less battery charging polarization and better electrochemical kinetic performance.
[0055] The discharge process (lower half of the figure, voltage drops from approximately 3.2V): After being fully charged, the battery begins to discharge. The voltage initially maintains a discharge plateau, then drops rapidly. At the same discharge capacity, the discharge voltages of Examples 1 and 2 are consistently higher than those of the three comparative examples. After approximately 2.0Ah of capacity, the voltage on all curves begins to decrease rapidly; approaching the 2.3-2.5Ah range, the voltage drops sharply, indicating that the battery is nearing discharge termination.
[0056] The comparison shows that the charge / discharge platform voltages of Examples 1-2 are superior to those of Comparative Examples 1-3, indicating that the batteries have less ohmic and electrochemical polarization. Under the same charge / discharge capacity, the voltage drop is smaller. Examples 1-2 can release slightly more effective capacity than the three comparative examples, resulting in higher usable energy. Examples 1-2 have a smoother charge / discharge platform and more stable battery operating voltage; Comparative Examples 1-3 have a larger discharge voltage drop.
[0057] 2. Rate performance: Comparison curves of potential change with SOC under 4C high-current fast charging conditions (see...) Figure 7 ): As shown in the figure, during the charging process, as the State of Charge (SOC) increases from 0% to 100%, lithium ions are inserted into the negative electrode, causing the negative electrode potential to drop rapidly, and then slowly approach 0V. In the low SOC range (0-10%), the negative electrode potential of all samples drops rapidly. The potentials of the three comparative examples (1-3) drop even faster, rapidly decreasing to near 0V within an SOC of approximately 12%. The curves of Examples 1-2 show a significant rightward shift: under the same negative electrode potential conditions, Examples 1-2 can achieve a higher SOC.
[0058] For example, with the same negative electrode potential of 0.02V, the comparative example has a SOC of approximately 10%, while Example 1 can achieve an SOC of approximately 22%. This demonstrates that the modified negative electrode of this invention can maintain a relatively higher negative electrode potential at a higher SOC.
[0059] High SOC range (>40%): All curve potentials approach 0V, the negative electrode is close to full lithium insertion state, and the curves tend to overlap.
[0060] Therefore, the curves of Examples 1-2 generally shift towards higher SOC: at the same SOC, the negative electrode potential of Examples 1-2 is higher than that of the Comparative Examples, which can effectively suppress lithium plating at the negative electrode during charging and improve battery charging safety. In Comparative Examples 1-3, the negative electrode potential drops rapidly, falling to an extremely low potential at a relatively low SOC, posing a risk of lithium plating in the early stages of charging.
[0061] 3. Cyclic performance (see...) Figure 8 and Figure 9 ): like Figure 8As shown, the horizontal axis represents the Cycle Number: the number of charge-discharge cycles of the battery, indicating the number of times the battery has been repeatedly charged and discharged. A higher value indicates a longer service life. The vertical axis represents Capacity Retention: the percentage of remaining battery capacity after a cycle relative to the initial capacity. A higher value indicates less capacity decay. 100% represents the initial capacity. Test conditions: 1C charging, 1C discharging, voltage range 2.75V-4.2V, which is a high-rate cycle test to accelerate battery life assessment.
[0062] Initial stage (0-200 cycles): The capacity retention rate of all samples briefly exceeds 100%, indicating battery activation; subsequently, the capacity of all samples begins to continuously decline. Mid-cycle range (200-1200 cycles): All five curves decline synchronously, but show clear stratification: Example 1 > Example 2 > Comparative Example 1 > Comparative Example 2 > Comparative Example 3. At the same number of cycles, the capacity retention rate of the examples is significantly higher than that of the comparative examples. Comparative Example 3 exhibits the fastest decline, reaching the 80% failure threshold after approximately 1100 cycles; Comparative Example 2 is next. Long-cycle range (after 1200 cycles): The three comparative examples decline rapidly in succession, reaching the 80% capacity failure point in turn; Examples 1 and 2 show slower decline rates, withstanding more cycles before reaching 80%, while Example 1 has the best cycle life, reaching nearly 1700 cycles before reaching the 80% capacity retention line.
[0063] Therefore, under 1C high-rate cycling conditions, the battery capacity decay rate of Examples 1-2 of the present invention is significantly lower than that of the three comparative examples; this proves that the improved solution of the present invention can suppress side reactions and impedance growth during battery cycling, and effectively improve the cycle life of the battery under high rate conditions.
[0064] like Figure 9 As shown, the horizontal axis represents the Cycle Number: the number of charge-discharge cycles, indicating the number of times the battery has been repeatedly charged and discharged. The vertical axis represents the Attenuation Rate: capacity degradation rate (%); degradation rate = (initial capacity - current capacity) ÷ initial capacity × 100%; the higher the value, the more capacity the battery loses, and the more severe the aging; a negative value corresponds to battery activation, with the capacity slightly higher than the initial capacity. Industry standard: a degradation rate of 20%, corresponding to a capacity retention rate of 80%, is considered the end of the battery's cycle life.
[0065] In the initial cycling phase (0-200 cycles): the curve shows a slight negative decay rate, corresponding to battery activation, with the actual usable capacity briefly exceeding the initial capacity, a common phenomenon in lithium batteries. Afterwards, the decay rate of all samples continues to climb. In the mid-cycle phase (200-1000 cycles), the decay rate of all samples increases with the number of cycles, and the curves show clear stratification: Example 1 < Example 2 < Comparative Example 1 < Comparative Example 2 < Comparative Example 3. Under the same cycle count, the capacity decay rate of the examples is significantly lower than that of the comparative examples. Comparative Example 3 has the steepest slope and the fastest capacity decay; followed by Comparative Example 2. In the long-cycle phase (after 1000 cycles): Comparative Example 3 reaches the 20% decay rate first, reaching the end of its lifespan earliest; Comparative Example 2 and Comparative Example 1 fail sequentially; Examples 1 and 2 have smaller overall slopes and a smoother decay process, requiring more cycles before the decay rate reaches 20%; Example 1 has the best performance, with the smallest capacity loss under the same cycle count.
[0066] Therefore, under 1C high-rate charge-discharge conditions, the capacity decay rate of the embodiment of the present invention is significantly lower than that of the comparative example; this indicates that the improved scheme of the present invention can effectively suppress side reactions during cycling, reduce battery capacity loss, and improve long-cycle reliability.
[0067] In summary, the high-capacity fast-charging graphite prepared by the present invention through an integrated liquid-phase fusion and gas-phase coating process exhibits superior structural stability and electrochemical performance compared to traditional single coating processes and stepwise modification processes. The integrated modification process can simultaneously complete the fusion and reconstruction of the internal structure of graphite and the coating of a dense carbon layer on the surface. It not only increases the lithium storage active sites inside the graphite and reconstructs the lithium-ion transport channels through liquid-phase modification, but also suppresses side reactions and reduces surface impedance through a uniform and dense gas-phase carbon coating layer. At the same time, it reduces secondary pollution and structural damage caused by stepwise processes, ultimately achieving a simultaneous improvement in the specific capacity, rate performance and cycle life of the graphite anode material, which is suitable for the application requirements of high-energy-density fast-charging lithium-ion batteries.
[0068] Those skilled in the art should understand that the discussion of any of the above embodiments is merely exemplary and is not intended to imply that the scope of the invention is limited to these examples; within the framework of the invention, the technical features of the above embodiments or different embodiments can also be combined, the steps can be implemented in any order, and there are many other variations of the different aspects of the invention as described above, which are not provided in detail for the sake of brevity.
[0069] This invention aims to cover all such substitutions, modifications, and variations that fall within the broad scope of the inventive concept. Therefore, any omissions, modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this invention should be included within the protection scope of this invention.
Claims
1. A method for preparing high-capacity fast-charging graphite by integrating liquid-phase fusion and gas-phase coating, characterized in that, Includes the following steps: S1. Pretreatment of graphite matrix: Place the graphite matrix in a vacuum drying oven and vacuum dry at 120-150℃ for 4-6 hours to obtain graphite powder. S2. Preparation of functional liquid phase modification system: Mix the modified carbon source, high capacity dopant and dispersing solvent evenly according to the mass ratio to prepare a uniform and stable liquid phase modification system. The high capacity dopant is selected from one or more of nano silicon oxide, lithium titanate and porous carbon micro powder. S3. Liquid-phase infiltration and fusion modification: Pretreated graphite powder is added to a liquid-phase modification system and stirred at 1200-2000 rpm for 30-60 minutes at room temperature to ensure that the liquid-phase modification system fully wets the graphite powder and penetrates into the internal pores and intergranular spaces of the graphite. Subsequently, in a closed high-temperature and high-pressure reactor, the pressure is increased to 1.5-4.0 MPa by inert gas, the temperature is raised to 180-250℃, and held at a constant temperature for 2-4 hours to complete the low-temperature fusion reaction of the liquid phase. This allows the liquid-phase modification system to be tightly bonded to the internal granular spaces of the graphite powder, reconstructing the internal porous transport structure, increasing lithium storage active sites, and obtaining a liquid-phase fusion modified graphite intermediate. S4. Integrated in-situ gas phase coating: After the liquid phase fusion reaction is completed, the pressure is released in the same reaction equipment and switched to an inert atmosphere and heated. A mixture of gas phase carbon source and inert carrier gas is introduced for gas phase deposition coating. A uniform and dense carbon coating layer is grown in-situ on the surface of the liquid phase fusion modified graphite intermediate. After the reaction is completed, it is naturally cooled to room temperature in an inert atmosphere. S5. Post-processing and molding: After natural cooling to room temperature, the material is sequentially screened, iron removed, and purified to obtain a high-capacity fast-charging graphite anode material.
2. The method for preparing high-capacity fast-charging graphite by integrating liquid-phase fusion and gas-phase coating according to claim 1, characterized in that: In step S1, the graphite matrix is one of natural graphite micro powder and artificial graphite powder.
3. The method for preparing high-capacity fast-charging graphite by integrating liquid-phase fusion and gas-phase coating according to claim 1, characterized in that: In step S1, the particle size D50 of the graphite matrix powder is 8-15 μm.
4. The method for preparing high-capacity fast-charging graphite by integrating liquid-phase fusion and gas-phase coating according to claim 1, characterized in that: In step S2, the mass ratio of each component in the liquid-phase modification system is: 5%-12% modified carbon source, 2%-5% high-capacity doping agent, and the balance is dispersion solvent.
5. The method for preparing high-capacity fast-charging graphite by integrating liquid-phase fusion and gas-phase coating according to claim 1, characterized in that: In step S2, the modified carbon source is selected from one or more of sucrose, glucose, phenolic resin liquid and asphalt solution.
6. The method for preparing high-capacity fast-charging graphite by integrating liquid-phase fusion and gas-phase coating according to claim 1, characterized in that: In step S2, the dispersing solvent is a mixture of anhydrous ethanol and deionized water, wherein the volume ratio of anhydrous ethanol to deionized water is 1:
1.
7. The method for preparing high-capacity fast-charging graphite by integrating liquid-phase fusion and gas-phase coating according to claim 1, characterized in that: In step S3, the solid-liquid mass ratio of the graphite powder to the liquid-phase modification system is 1:3-5.
8. The method for preparing high-capacity fast-charging graphite by integrating liquid-phase fusion and gas-phase coating according to claim 1, characterized in that: In step S4, the inert atmosphere is either nitrogen or argon. The heating rate is 5-10℃ / min, and the temperature is increased to 800-950℃; The gaseous carbon source is selected from one or more of propylene, acetylene, and methane; The gaseous carbon source accounts for 10%-20% of the volume in the mixed gas. The vapor deposition coating time is 1.5-3 hours.
9. The method for preparing high-capacity fast-charging graphite by integrating liquid-phase fusion and gas-phase coating according to claim 1, characterized in that: In step S4, the thickness of the carbon coating layer is 20-50 nm.